Nonlinear Damping Output-Feedback Voltage Control for DC/DC Converters via Model-Independent Voltage Derivative Observer - Kim, Seok Kyoon; Lim, Sun; Lee, Kyo Beum (IEEE Transactions on Industrial Electronics, 2023)
This paper proposes an output-feedback solution for DC/DC converter applications that considers model-plant mismatches and load variations as constraints in industrial applications. The following two major contributions of this study are particularly advantageous: (a) nonlinear damping terms to inject the critical damping performance into the closed-loop system with the cooperation of the feedback gain structure depending on the damping coefficients, and (b) estimation of the output voltage derivative by the model-independent observer with only one simple closed-loop eigenvalue and current feedback removal. The experimental study highlights the practical merit of the proposed solution by demonstrating the critical damping performance that suppresses the peak current level using a 3-kW bidirectional DC/DC converter.
Keywords: Critical damping; Critical damping injection; Damping injection; Inductor; Load modeling; Nonlinear damping; Observer; Order reduction; Output-feedback; Voltage derivative observer; Critical damping injection; order reduction; power converter; voltage derivative observer